Comparison of SAW, AHP, and TOPSIS Methods in Improving the Quality of Supplier Selection Results at PT. Selamat Sempurna Tbk - Rosiana, Dhini; Abidin, Abidin (Jurnal Ilmiah Teunuleh, 2025)
Suppliers are a crucial element in the supply chain with a significant impact on the continuity of production processes. PT. Selamat Sempurna Tbk., located in Tangerang, is an automotive component industry that collaborates with several packaging suppliers (Duplek). However, the supplier selection process is still subjective, and a decision-making method has not yet been established. The diverse standards set by suppliers make the selection process less effective. In line with this issue, PT. Selamat Sempurna Tbk. requires decision-making methods, namely SAW, AHP, and TOPSIS. Through interviews with relevant stakeholders, supplier selection criteria are identified, weighted, and assigned levels of importance. The criteria include product quality, delivery capability, warranty, ISO certification ownership status, price, and minimum order quantity. The calculation process involves comparing the three methods. Based on the research findings, the SAW method selected PT. PHI (0.958), while the AHP method (0.256) and the TOPSIS method (0.891) selected PT. PGU. The final evaluation results of the three methods indicate differences in values and rankings, as each method employs different approaches in evaluating supplier selection criteria. Among the three methods, it can be concluded that the SAW method is easier to understand but pays less attention to the interrelationships between criteria. The AHP method places greater emphasis on pairwise weighting processes, whereas the TOPSIS method provides clearer results by comparing distances to ideal solutions, but it requires precise comparative data for accurate results.